A DR Loaded Substrate Integrated Waveguide Antenna for 60 GHz High Speed Wireless Communication Systems - Nadeem Ashraf; Hamsakutty Vettikalladi; Majeed A. S. Alkanhal (International Journal of Antennas and Propagation, 2014)
The concept of substrate integrated waveguide (SIW) technology along with dielectric resonators (DR) is used to design antenna/array for 60 GHz communication systems. SIW is created in the substrate of RT/duroid 5880 having relative permittivity εr=2.23 and loss tangent tan⁡δ=0.003. H-shaped longitudinal slot is engraved at the top metal layer of the substrate. Two pieces of the DR are placed on the slot without any air gap. The antenna structures are modeled using CST Microwave Studio and then the results are verified using another simulation software HFSS. Simulation results of the two designs are presented; first a single antenna element and then to enhance the gain of the system a broadside array of 1×4 is presented in the second design. For the single antenna element, the impedance bandwidth is 10.33% having a gain up to 5.5 dBi. Whereas in an array of 1×4 elements, the impedance bandwidth is found to be 10.70% with a gain up to 11.20 dBi. For the single antenna element and 1×4 antenna array, the simulated radiation efficiency is found to be 81% and 78%, respectively.